Cloning of MiRNA 19b and MiRNA 92a genes from HEPG2 cancer cell lines and MCF-7 cancer cell lines / Muhammad Syafiq Afandi Mahdan - Mahdan, Muhammad Syafiq Afandi (2013)
MicroRNAs (miRNAs or miRs) are small RNA molecules of approximately 22 to 28 nucleotides which a class of endogenous encoded non-coding RNAs that control gene expression. Previous researchers suggested that miRNAs were highly expressed in human resulting to the development of various cancerous cells including the liver cancer cell (HepG2) and breast cancer cell (MCF-7). This study aims to clone the miRNA l 9b and miRNA 92a from HepG2 and MCF-7 cancer cell lines by using a set of specific primer designed with NCBI Genebank. First and foremost, the miRNA 19b and miRNA 92a from HepG2 and MCF-7 cancer cell lines as well as WRL healthy cell line was amplified using .polymerase chain reaction (PCR). However, WRL cell line was discontinued in the bulk PCR. The optimum annealing temperature used was 63. I °C after several optimization processes was done. Clear band was observed under the UV light. PCR product was further cloned using TA cloning method. Successful cloning was screened through blue white screening procedure. White colonies were observed in agar plates. This indicated the successful ligation of the vector and inserts which is miRNAs from HepG2 and MCF-7. The resulting white colony was propagated 16 hours. Plasmid identification was done to ensure white colony contain the plasmid and desired insert. In order to prove that there was an insert in the vector, PCR by using M 13 primers and sequence analysis was carried out. The size of PCR product was expected approximately 488bp. Through sequence analysis, both sequences for HepG2 and MCF-7 were aligned according to NCBI Genebank sequences.